ANALISIS PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA MELAKUKAN PENEBANGAN POHON DALAM KAWASAN HUTAN TANPA IJIN YANG BERWENANG - Sukoco SP; Erlina B; Eddy S Wirabhumi (Law Faculty of Universitas Bandar Lampung, 2019)
The social phenomena that occurred today are still encountered cases related to the criminal acts of illegal logging in forest areas. One of the cases that have occurred is the criminal act of logging the tree in the forest area without the authorized permission. The problems in this study include: whether the cause of perpetrators to commit crimes in forest areas without authorized permits, how criminal liability against perpetrators of criminal acts Logging in forest areas without authorized permits. The results of research and settlement indicate that the cause of perpetrators to commit criminal acts of logging in forest areas without authorized permits include intrinsic factors (poor family environment, age and intelligence , and psychology of evil talent, personality), extrinsic factors (low level of education, social environment, intention and opportunity), weak religious education and ethics, lack of environmental education and forestry, lack of supervision. The advice in this research is expected to law enforcement officers with the forestry service in order to provide strict sanctions against perpetrators of criminal acts of logging in forest areas without authorized permits.